Development of Exponent workbook content characterized with RME for Technical Vocational High School Students - Sri Widowati (Jurnal Pendidikan Sains, 2013)
Pengembangan Buku Kerja Materi Eksponen Bercirikan RME untuk Siswa SMK Teknik Abstract: The research objective of this development is to produce English-language workbook material characterized exponent Realistic Mathematics Education (RME) for students Vocational High School (SMK) technique class X as well as valid criteria, practical and effective. Expert validation process was conducted to determine the level of validity workbook generated. The process of testing conducted to determine the level of practicality and effectiveness of the workbook is generated. Based on the validation process, the result that the resulting workbook meet valid category. While the process of testing found that the feasibility study using the workbook is on practical criteria. In addition, the average students gave positive responses and the results of the test showed that there is a classical completeness. Based on pre-defined criteria, then the workbook produced valid criteria, practical and effective. Key Words: workbook, exponent, RME, technical vocational high school Abstrak: Tujuan penelitian pengembangan ini adalah menghasilkan buku kerja berbahasa Inggris materi eksponen yang bercirikan Realistic Mathematics Education (RME) untuk siswa Sekolah Me-nengah Kejuruan (SMK) teknik kelas X serta memenuhi kriteria valid, praktis dan efektif.  Proses vali-dasi ahli dilakukan untuk mengetahui tingkat kevalidan buku kerja yang dihasilkan. Proses uji coba dilakukan untuk mengetahui tingkat kepraktisan dan keefektifan dari buku kerja yang dihasilkan. Berdasarkan proses validasi, diperoleh hasil bahwa buku kerja yang dihasilkan memenuhi kategori valid. Sedangkan dari proses uji coba diperoleh bahwa keterlaksanaan pembelajaran dengan menggu-nakan buku kerja berada pada kriteria praktis. Selain itu, rata-rata siswa memberikan respon positif  dan hasil tes menunjukkan terdapat ketuntasan secara klasikal. Berdasarkan kriteria yang telah ditetap-kan, maka buku kerja yang dihasilkan memenuhi kriteria valid, praktis dan efektif. Kata kunci: buku kerja, eksponen, RME, sekolah menengah kejuruan teknik